Optimized Pt Loaded Cerium Tungstate Electrochemical Sensor for Rapid Response and Recovery NO2 Detection - Jiaxin Li; Xichao Mo; Chonghui Zhu; Minghui Yang (Advanced Sensor Research)
Abstract Nitrogen dioxide (NO2) is a dangerous environmental pollutant that poses a risk to human health and ecosystems, leading to respiratory disease and environmental degradation. Current detection methods often suffer from high power consumption, environmental sensitivity, and limited stability. In this study, an electrochemical gas sensor synthesized by calcination and hydrothermal method is presented using cerium tungstate (Ce2(WO4)3) as a support material doped with 0.5 wt.% platinum (Pt). The sensor has a detection limit as low as 0.5 ppm, a response time of 27.1 s, and a recovery time of 7.9 s at room temperature. It also has better selectivity for NO2 than other gases and good humidity resistance. The improved sensing performance is attributed to the increase in oxygen vacancy concentration and the favorable interaction between Pt and Ce2(WO4)3, which promotes active site formation and catalytic efficiency. These results highlight the potential of Pt/Ce2(WO4)3 as an effective and energy‐efficient sensor for NO2 detection, providing a new approach for real‐time monitoring with fast recovery and high selectivity.